The adventures of Tom Sawyer - Twain, Mark 1835-1910 (Washington, D. C. : Office of English Language Programs, 2005)
The adventures of Tom Sawyer stands aot as one of the great American novels, with adventure, humor, danger, and warmth. It is filled with characters that have become part of american culture: Tom, Huck Finn, Becky, Aunt Polly, and others
Las aventuras de Tom Sawyer se destacan como una de las grandes novelas estadounidenses, con aventura, humor, peligro y calidez. Está lleno de personajes que se han convertido en parte de la cultura estadounidense: Tom, Huck Finn, Becky, tía Polly y otros.
CONTENTS 1. AUNT POLLY DECIDES HER DUTY 2. STRONG DESIRE - WISE ACTION 3. TOM AS AN ARMY OFFICER-DELIGHTFUL SADNESS 4. GOING TO SUNDAY SCHOOL 5. IN CHURCH AND OTHERS
For students of English as a Foreign Language
Para estudiantes de inglés como lengua extranjera.
Keywords: NORTH AMERICAN LITERATURE -- ADVENTURE STORIES; LITERATURA NORTEAMERICANA -- HISTORIAS DE AVENTURAS